2012
DOI: 10.1021/jf302242n
|View full text |Cite
|
Sign up to set email alerts
|

Transepithelial Transport of Theasinensins through Caco-2 Cell Monolayers and Their Absorption in Sprague–Dawley Rats after Oral Administration

Abstract: The aim of this study is to illustrate the in vivo and in vitro absorption of theasinensins B and A that are (-)-epigallocatechin-3-O-gallate (EGCG)-(-)-epigallocatechin (EGC) dimer and EGCG dimer, respectively, and their transport pathway across the intestinal membrane. Our animal study by a single oral administration to rats demonstrated the intact absorption of theasinensins into the blood system, which was estimated to be a >10-fold lower absorption amount than EGCG. The in vitro absorption study indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 33 publications
(82 reference statements)
0
22
0
Order By: Relevance
“…It was reported that a concentration of 25 μg/ml of proanthocyanidins is need in vitro to reach the significant regulation of miRNA [56]. Results from Qiu et alindicated that after a single oral administration of 100 mg/kg body weight for each compound, the plasma concentrations of EGC and EGCG dimer were 7.5 and 9.3 nmol/L, separately [57]. and their metabolites (about 17.18 μmol/L in total) were five times higher than that in the cell media at 25 μg/ml of proanthocyanidins [56].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It was reported that a concentration of 25 μg/ml of proanthocyanidins is need in vitro to reach the significant regulation of miRNA [56]. Results from Qiu et alindicated that after a single oral administration of 100 mg/kg body weight for each compound, the plasma concentrations of EGC and EGCG dimer were 7.5 and 9.3 nmol/L, separately [57]. and their metabolites (about 17.18 μmol/L in total) were five times higher than that in the cell media at 25 μg/ml of proanthocyanidins [56].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Thus far, no study has been conducted on theasinensin absorption, except for a report by Qiu et al (2012), who outlined the intact absorption of dimeric catechins (TSA and TSB) in SpragueDawley (SD) rats (100 mg/kg) via TJ-paracellular passive diffusion (Fig. 2).…”
Section: Absorption Of Theasinensinsmentioning
confidence: 99%
“…Absorption experiment of theasinensins to SD rat was performed by a single oral administration of TSA (100 mg/kg). The inserted chromatogram by electrochemical detector-high performance liquid chromatography (HPLC-ECD, 500 mV for working electrode) shows rat plasma profile obtained at 60 min after the administration of TSA (cited from the report by Qiu et al (2012)). An LC-TOF-MS chromatogram of theaflavins was obtained from Caco-2 cell transport experiments, in which transport of 1 mM TF3′G across Caco-2 cell monolayers for 60 min was performed, and solutions obtained at apical and basolateral sides analyzed by MS in negative ionization mode.…”
Section: Absorption Of Theasinensinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transport experiments on hCMEC/D cell monolayer were conducted as described previously with minor modifications (Qiu et al, 2012). After hCMEC/D cell monolayers were observed on the transwells of 24 wells using a hemocytometer under a microscope, hCMEC/D3 cell monolayer integrities were examined by measuring transepithelial electrical resistances (TEER) with an electrical resistance system.…”
Section: Transport Of Ginkgolides Across Hcmec/d3 Cell Monolayermentioning
confidence: 99%